2017
DOI: 10.1093/ckj/sfx062
|View full text |Cite
|
Sign up to set email alerts
|

Environmental toxin-induced acute kidney injury

Abstract: Human beings are exposed to various potentially toxic agents and conditions in their natural and occupational environments. The kidney, due to its concentrating ability and excretory function, is highly vulnerable to the effects of environmental toxins. Identifying the precise cause and mechanisms of environmentally induced renal injury remains a challenge for which various scientific disciplines need to be involved. Investigations in this field are confronted with the apparent infinite types of toxins, their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(35 citation statements)
references
References 153 publications
(140 reference statements)
1
33
0
1
Order By: Relevance
“…Since then, AAN has raised worldwide attention (Jadot et al, 2017). Long-term ingestion of herbal formula known or suspected to contain AAs is one of the prominent risk factors for developing AAN (Jia et al, 2005; Vervaet et al, 2017). Although the sale and use of AA-containing products are banned or restricted in most of the countries (Krell and Stebbing, 2013), AAN induced by numerous herbal remedies and products are still reported from all over the world (Lord et al, 1999; Yang et al, 2006; Debelle et al, 2008; Shaohua et al, 2010; Wu et al, 2012; Vaclavik et al, 2014; Ban et al, 2018).…”
Section: Aristolochic Acid-induced Adverse Reactionsmentioning
confidence: 99%
“…Since then, AAN has raised worldwide attention (Jadot et al, 2017). Long-term ingestion of herbal formula known or suspected to contain AAs is one of the prominent risk factors for developing AAN (Jia et al, 2005; Vervaet et al, 2017). Although the sale and use of AA-containing products are banned or restricted in most of the countries (Krell and Stebbing, 2013), AAN induced by numerous herbal remedies and products are still reported from all over the world (Lord et al, 1999; Yang et al, 2006; Debelle et al, 2008; Shaohua et al, 2010; Wu et al, 2012; Vaclavik et al, 2014; Ban et al, 2018).…”
Section: Aristolochic Acid-induced Adverse Reactionsmentioning
confidence: 99%
“…Recently, Sun et al (2012) reported that melamine was gradually degraded into cyanuric acid by rumen microorganisms in lactating dairy cows (Sun et al 2012). It seems that the addition of melamine is to increase nitrogen levels in fertilizer and animal food, consequently, measurement of protein levels is uncertain because many methods mainly estimate amount of nitrogen in the substrates (Dalal & Goldfarb 2011;Hau et al 2009;Vervaet et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…High levels of metals (e.g. As or Cd) can induce acute kidney injury and have been proposed as biomarkers of kidney injury of other types, however it is unclear if, or at what levels, these metals cause chronic kidney injury (29).…”
Section: Key Resultsmentioning
confidence: 99%